Integrating exosome wide associations study and Mendelian randomization identified causal miRNAs for type 2 diabetes mellitus and its complications - Dong-Ling Li; Xin-Yi Ding; Qiao-Ling He; Wan-Hua Zhan; Juan Long; Mei-Nan He; Jia-Lu Zhang; Qing-Xiang Zeng; Na Lu; Yong-Qian Chi; Meng-Chen Zou (Diabetology & Metabolic Syndrome)
Abstract Background Type 2 diabetes mellitus (T2DM) and its complications, including diabetic lower extremity arterial disease (DLEAD) and diabetic foot (DF), impose significant health burdens worldwide. However, the differential expression of microRNAs (miRNAs) between T2DM and its complications and its causal effects remain poorly understood. Methods We conducted an exosome-wide association study (EWAS) comparing miRNA profiles between T2DM and its complications, including DLEAD and DF, without healthy controls. The significant miRNAs identified between DM and its complications were further validated by integrating cis-miRNA expression quantitative trait loci (cis-miR-eQTLs) and genome-wide association study (GWAS) summary data of T2DM and peripheral arterial disease (PAD) through two-sample Mendelian randomization (MR) analysis. Results We identified several differential expressions of miRNAs between T2DM, DLEAD, and DF, such as hsa-miR-409-3p between T2DM and DLEAD, hsa-miR-543 between T2DM and DF and hsa-miR-206 between DLEAD and DF. The two sample MR analysis revealed potential causal relationships between dysregulated miRNAs and T2DM and its complications, such as hsa-miR-30b-3p and hsa-miR-30b-5p showed causal associations with T2DM and PAD respectively. Conclusions Our study elucidates the miRNA signatures associated with T2DM and its complications. These findings provide insights into the pathogenesis of T2DM and its complications and suggest potential therapeutic targets for intervention.